2019
DOI: 10.1021/acs.chemmater.9b04520
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Orthogonal AIEgen for Specific Discrimination and Elimination of Bacterial Pathogens via Metabolic Engineering

Abstract: Multiple bacterial infections caused by interpatient spread lead to complications in diagnosis and clinical management, seriously threatening human health. In this contribution, we design a bio-orthogonal fluorescence turn-on probe TPEPA for the discrimination and precise ablation of bacterial pathogens. The probe has good water solubility and negligible fluorescence in aqueous media. On clicking with the azide groups decorated on bacteria by metabolic engineering, it shows fluorescence turn-on with far-red/ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 59 publications
0
62
0
Order By: Relevance
“…Thus, FRET could not occur, which results in a considerable 1 O 2 generation to kill the bacteria. In another work, Liu’s group 248 has designed a red-emissive AIE photosensitizer that can interact with metabolically treated Gram-negative bacteria with 8-azido-3,8-dideoxy- d -manno-octulosonic acid (Kdo-N3) and Gram-positive bacteria with 3-azido- d -Alanine hydrochloride ( d -Ala-N 3 ), respectively, for bacteria detection. The bacteria targeting an AIE-PS molecule in this study possess a good SOG ability for the detection and effective treatment of bacterial infection.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Thus, FRET could not occur, which results in a considerable 1 O 2 generation to kill the bacteria. In another work, Liu’s group 248 has designed a red-emissive AIE photosensitizer that can interact with metabolically treated Gram-negative bacteria with 8-azido-3,8-dideoxy- d -manno-octulosonic acid (Kdo-N3) and Gram-positive bacteria with 3-azido- d -Alanine hydrochloride ( d -Ala-N 3 ), respectively, for bacteria detection. The bacteria targeting an AIE-PS molecule in this study possess a good SOG ability for the detection and effective treatment of bacterial infection.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Additionally, for deep tissue infection, phototherapy cannot be used unless the site of infection has been identified, which severely limits its clinical use in antibacterial infections treatment. Moreover, a consensus has been reached among researchers worldwide that the patient survival rate can be greatly increased if the disease is effectively diagnosed and treated at the early stage 193 , 194 . Based on this investigation, Wang et al reported a magnetic nanosystem combined with photodynamic treatment, which could identify bacterial species for early sepsis diagnosis and extracorporeal photodynamic blood disinfection 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantages of its high specificity, various examples based on AIEgens have been developed for cancer theranostics as well as bacterial labeling, identification, and killing. [ 104–109 ]…”
Section: Turn‐on Theranostics Based On In Situ Aggregationmentioning
confidence: 99%
“…(B) Schematic illustration of TPEPA for discrimination and precise ablation of bacterial pathogens by metabolic labeling followed by click reaction. Reproduced with permission: Copyright 2020, American Chemical Society [108] . (C) Design and characterization of the developed TPACN‐ D ‐Ala probe for bacteria tracking and photodynamic killing in vivo , as well as the illustration of metabolic labeling process.…”
Section: Turn‐on Theranostics Based On In Situ Aggregationmentioning
confidence: 99%
See 1 more Smart Citation